Perspectives of Italian pregnant women on pregnancy examinations and pregnancy care: is the caregiver more important than the care? - Indraccolo, Ugo; Cona, Simona; Nistor, Alexandra; Indraccolo, Salvatore Renato; Di Iorio, Romolo; Fedeli, Piergiorgio; De Angelis, Carlo (Acta Biomedica Atenei Parmensis, 2021)
Aim. Assessing awareness of Italian low-risk pregnant patients on low-risk pregnancy care and what do they feel about their own pregnancy. Methods. A questionnaire was administered to 382 low-risk pregnant women. This questionnaire assessed general knowledge of low-risk pregnancy, low-risk pregnancy care, and how much patients rated ten topics of low-risk pregnancy care. It would be expected that the knowledge of each topic would associates with the patient’s perceived importance of that topic. Results. Poor knowledge of pregnancy care was proven. Patients seem to incorrectly overrate vaginal examinations and obstetric and gynecologist-led care, while they attribute appropriate importance to midwife-led care. The more examinations performed (vaginal examinations, sonographic checks, cardiotocographies), the higher their rating. Conclusions. In Italy, expectations of pregnant women about their own pregnancy are incorrectly trusted in the obstetrics and gynecologists. Both poor knowledge of pregnancy care and cultural perspectives on the birth process amongst Italian people explain the finding. Referring low-risk pregnant women to midwives would help them to rate more the care than the caregiver.